Role of integrin α2β1 in mediating osteoblastic differentiation on three‐dimensional titanium scaffolds with submicron‐scale texture. Issue 6 (16th September 2014) - Wang, Xiaokun; Schwartz, Zvi; Gittens, Rolando A.; Cheng, Alice; Olivares‐Navarrete, Rene; Chen, Haifeng; Boyan, Barbara D.
Abstract Hierarchical surface roughness of titanium and titanium alloy implants plays an important role in osseointegration. In vitro and in vivo studies show greater osteoblast differentiation and bone formation when implants have submicron‐scale textured surfaces. In this study, we tested the potential benefit of combining a submicron‐scale textured surface with three‐dimensional (3D) structure on osteoblast differentiation and the involvement of an integrin‐driven mechanism. 3D titanium scaffolds were made using orderly oriented titanium meshes and microroughness was added to the wire surface by acid‐etching. MG63 and human osteoblasts were seeded on 3D scaffolds and 2D surfaces with or without acid etching. At confluence, increased osteocalcin, vascular endothelial growth factor, osteoprotegerin (OPG), and alkaline phosphatase (ALP) activity were observed in MG63 and human osteoblasts on 3D scaffolds in comparison to 2D surfaces at the protein level, indicating enhanced osteoblast differentiation. To further investigate the mechanism of osteoblast‐3D scaffold interaction, the role of integrin α2β1 was examined. The results showed β1 and α2β1 integrin silencing abolished the increase in osteoblastic differentiation markers on 3D scaffolds. Time course studies showed osteoblasts matured faster in the 3D environment in the early stage of culture, while as cells proliferated, the maturation slowed down to a comparative level as 2D surfaces. After 12 days of postconfluent culture, osteoblasts on 3D scaffolds showed a second‐phase increase in ALP activity. This study shows that osteoblastic differentiation is improved on 3D scaffolds with submicron‐scale texture and is mediated by integrin α2β1. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1907–1918, 2015.